2022
DOI: 10.1002/emp2.12718
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department use and hospital admissions among adult orthotopic heart transplant patients

Abstract: Objective To study the demographics, clinical presentations, and outcomes of emergency department (ED) visits of patients with heart transplantation (HT) in the United States. Methods We performed a secondary analysis of the National Emergency Department Sample database from 2016 to 2018. All ED visits of patients with HT aged ≥ 18 years were identified using International Classification of Diseases, Tenth Revision codes. Results Out of a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…In our analysis, as in the study by Pothuru et al, 7 most ED encounters were for noncardiac conditions, with infection being most common, which reinforces prior findings and has important implications. Infection has been shown to be a leading cause of morbidity and consequently readmission after transplant 12 , and prior studies of smaller cohorts have shown that infection is the most common reason for patients with HTs to present to the ED.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our analysis, as in the study by Pothuru et al, 7 most ED encounters were for noncardiac conditions, with infection being most common, which reinforces prior findings and has important implications. Infection has been shown to be a leading cause of morbidity and consequently readmission after transplant 12 , and prior studies of smaller cohorts have shown that infection is the most common reason for patients with HTs to present to the ED.…”
Section: Discussionsupporting
confidence: 88%
“…The most common cause for presentation was sepsis, followed by acute kidney injury and chest pain. 7 Our work confirms and adds to these findings in a much larger, and longitudinal, cohort of patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations